Reduced Cortical Complexity in Cirrhotic Patients with Minimal Hepatic Encephalopathy - Qiu-Feng Chen; Xiao-Hong Zhang; Tian-Xiu Zou; Nao-Xin Huang; Hua-Jun Chen (Neural Plasticity)
Purpose. Gray matter volume loss, regional cortical thinning, and local gyrification index alteration have been documented in minimal hepatic encephalopathy (MHE). Fractal dimension (FD), another morphological parameter, has been widely used to describe structural complexity alterations in neurological or psychiatric disease. Here, we conducted the first study to investigate FD alterations in MHE. Methods and Materials. We performed high-resolution structural magnetic resonance imaging on cirrhotic patients with MHE (n=20) and healthy controls (n=21). We evaluated their cognitive performance using the psychometric hepatic encephalopathy score (PHES). The regional FD value was calculated by Computational Anatomy Toolbox (CAT12) and compared between groups. We further estimated the association between patients’ cognitive performance and FD values. Results. MHE patients presented significantly decreased FD values in the left precuneus, left supramarginal gyrus, right caudal anterior cingulate cortex, right isthmus cingulate cortex, right insula, bilateral pericalcarine cortex, and bilateral paracentral cortex compared to normal controls. In addition, the FD values in the right isthmus cingulate cortex and right insula were shown to be positively correlated with patients’ cognitive performance. Conclusion. Aberrant cortical complexity is an additional characteristic of MHE, and FD analysis may provide novel insight into the neurobiological basis of cognitive dysfunction in MHE.